Evaluation of analgesic and anti-inflammatory activity of ethanolic extract of Enhydra fluctuans on male wistar rats - Roy, Kishor Kumar; Mollah, Md. Kabirul Islam; Reja, Md. Masud; Shil, Dibyendu; Maji, Ranjan Kumar (Journal of Applied Pharmaceutical Research, 2021)
Enhydra fluctuations an edible semi-aquatic vegetable plant are widely used in the traditional system of medicine. Ethanolic extract of Enhydra fluctuans was screened for analgesic & anti-inflammatory activity. Analgesic activity was evaluated by the hot plate method and anti-inflammatory activity was evaluated by formalin induce paw edema in Wistar rats (male). Ethanolic extract dose of 300 mg/kg reduce formalin induce paw inflammation and also increased the pain threshold in rats evidenced by hot plate method. The experimental results concluded that Enhydra fluctuans have significant analgesic and anti-inflammatory activity may due to flavonoid and phenolic compound content.